A conductive film of chitosan-polycaprolcatone-polypyrrole with potential in heart patch application. (May 2019) - Talebi, A.; Labbaf, S.; Karimzadeh, F.
Abstract: In this study, a novel polycaprolactone/chitosan/polypyrrole (PCL/chitosan/PPy) conductive composite film was fabricated. A polymer blend of PCL/chitosan (7:3) was selected and then 1, 2.5, 5 and 7.5 wt% of PPy was added to each solution. The addition of PPy to the PCL/chitosan blend resulted in decreased surface pit size and at higher concentration of PPy a porous structure was detected. The electrical conductivity of PCL/chitosan was 0.0164 ± 0.008 mS/m but increased to 0.55 ± 0.03 mS/m with the addition of 7.5% PPy. Hydrophilicty also improved with the addition of PPy as water contact angle changed from 107 ± 2.1° for PCL/chitosan to 101 ± 3.5° at 7.5% PPy. The tensile strength increased from 7.57 MPa for PCL/chitosan sample to 18.06, 16.02, 15.33 and 13.87 MPa for 1, 2.5, 5 and 7.5 wt% PPy, respectively. The films containing PPy had improved antibacterial properties against E. coli and S. aureus . Highlights: Fabrication of PCL/chitosan/polypyrrole (PPy) conductive composite film. Significant increase in the electrical conductivity of the films was detected with the addition of PPy. The tensile strength increased to 18.06 MPa with the addition of only 1 wt% PPy. Enhanced improvement in electrical conductivity was detected at increased concentrations of PPy. The films containing PPy had improved antibacterial properties against E. coli and S. aureus .